Deviation from Slow-Roll Regime in the EGB Inflationary Models with r ∼ <semantics><msubsup>Ne−1</msubsup></semantics> - Ekaterina O. Pozdeeva (Universe, 2021)
We consider Einstein–Gauss–Bonnet (EGB) inflationary models using the effective potential approach. We present evolution equations in the slow-roll regime using the effective potential and the tensor-to-scalar ratio. The choice of the effective potential is related to an expression of the spectral index in terms of e-folding number <semantics>Ne</semantics>. The satisfaction of the slow-roll regime is mostly related to the form of the tensor-to-scalar ratio r. The case of <semantics>r∼1/<msubsup>Ne2</msubsup></semantics> leads to a generalization of <semantics>α</semantics>-attractors inflationary parameters to Einstein–Gauss–Bonnet gravity with exponential effective potential. Moreover, the cosmological attractors include models with <semantics>r∼1/Ne</semantics>. And we check the satisfaction of the slow-roll regime during inflation for models with <semantics>r∼1/Ne</semantics>.